Endothelial cell malignancies in infants, children and adolescents: Treatment results of three Cooperative Weichteilsarkom Studiengruppe (CWS) trials and one registry. Issue 3 (8th December 2019) - Sparber‐Sauer, Monika; Koscielniak, Ewa; Vokuhl, Christian; Schmid, Irene; Bien, Ewa; Seitz, Guido; Hallmen, Erika; von Kalle, Thekla; Scheer, Monika; Münter, Marc; Bielack, Stefan S.; Niggli, Felix; et al.
Abstract: Background: Endothelial cell malignancies are extremely rare in childhood. New identification of genetic abnormalities (WWTR1:CAMTA1 translocation) helps to recognize potential therapeutic targets. Little is known about treatment and outcome of these patients. Methods: Clinical course, treatment, and outcome in patients with endothelial cell malignancies treated within the Cooperative Weichteilsarkom Studiengruppe (CWS) trials CWS‐91, ‐96, ‐2002P, and the Soft‐Tissue Sarcoma Registry (SoTiSaR) were analyzed (1991‐2019). Results: Patients had angiosarcoma (AS) ( n  = 12), malignant epithelioid hemangioendothelioma (EHE) ( n  = 16), and kaposiform hemangioendothelioma (KHE) ( n  = 13). The median age was 5.39 years (range, 0.8‐17.34); 33 patients had localized disease (LD), and 8 patients had metastatic disease. Therapy consisted of chemotherapy (CHT) (AS n  = 8, EHE n  = 9, KHE n  = 5), interferon or new agent therapy (EHE n  = 5, 2 KHE n  = 2), microscopically or macroscopically complete resection (AS n  = 3, EHE n  = 6, KHE n  = 3), and radiotherapy (AS n  = 6, EHE n  = 2, KHE n  = 1). Two patients (KHE) had watch‐and‐wait strategy resulting in stable disease. Complete remission (CR) was achieved in AS (10/12; 83%), EHE (10/16; 63%), and KHE (5/13; 38%). The five‐year EFS and OS for patients with AS was 64% (± 29 CI 95%) and 80% (± 25, CI 95%), with EHE 62% (± 24, CI 95%) and 78% (± 23, CI 95%), with KHE 33% (± 34, CI 95%) and 92% (± 15, CI 95%), respectively. Complete resection was a significant prognostic factor for AS, LD for EHE. Conclusions: Endothelial cell malignancies in childhood have a fair outcome with multimodal treatment. New treatment options are needed for metastic disease.